Protein malnutrition during gestation and early life decreases neuronal size in the medial prefrontal cortex of post-pubertal rats - Cruz-Rizzolo, Roelf J. [UNESP] (2017)
Retrospective studies in human populations indicate that protein deprivation during pregnancy and early life (early protein malnutrition, EPM) is associated with cognitive impairments, learning disabilities and may represent a risk factor for the late onset of some psychiatric disorders, fundamentally schizophrenia, a condition where the prefrontal cortex plays an important role. The purpose of this study was to analyze whether EPM affects structural aspects of the rat medial prefrontal cortex (mPFC), such as cortical volume, neuronal density and neuronal soma size, which seem altered in patients with schizophrenia. For this, a rat model of EPM (5% casein from conception to postnatal day 60) was adopted and the rat mPFC volume, total number of neurons and average neuronal volume were evaluated on postnatal day 60 (post-pubertal animals) by histo- and immunohistochemical techniques using unbiased stereological analysis. EPM did not alter the number of NeuN+ neurons in the rat mPFC. However, a very significant decrease in mPFC volume and average neuronal size was observed in malnourished rats. Although the present study does not establish causal relationships between malnutrition and schizophrenia, our results may indicate a similar structural phenomenon in these two situations. (C) 2017 The Authors. Published by Elsevier Ltd on behalf of International Brain Research Organization. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).